A Three-Level Single Stage A-Source Inverter With the Ability to Generate Active Voltage Vector During Shoot-Through State - Kheyrati, Mohammad Reza; Rajaei, Amirhossein; Tehrani, Vahid Moradzadeh; Mirzavand, Ghazal; Shahparasti, Mahdi (IEEE, 2022)
Single-stage boosting capability of impedance network (IN) inverters makes this family of inverters an attractive choice for DC/AC applications with low input DC voltage. A specific time of shoot-through (ST) state is required to achieve the required voltage gain. Conventionally ST state and zero output voltage vector should be applied simultaneously. This constraint limits the modulation index and increases the voltage stress of the semiconductor devices, particularly for applications requiring a high boosting factor. In this paper, as the boosting stage for a three-level inverter, a new modified configuration of A-source IN with two series outputs is proposed and connected to a 10-switches three-level inverter. Besides generating two outputs by a single IN, the proposed DC/AC inverter is able to apply an active voltage vector during the ST state. This capability improves the DC/AC voltage gain, increases the modulation index, and decreases the required ST time. The operation principles are described, and the steady-state relations are derived. It is compared with other magnetically coupled INs in terms of boost factor and voltage stress of switches. Considering the 10-switches three-level inverter as the front-end inverter, an adopted maximum boost strategy using the space vector modulation is developed targeting minimum ST time. Finally, a laboratory prototype of the converter is developed, and several tests are carried out. The results validate the given theories and simulations.
Keywords: Impedance source network; A-Source impedance network; multi-level inverter; maximum boost space vector; PWM; fi=Sähkötekniikka|en=Electrical Engineering|